2013
DOI: 10.2196/jmir.2784
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Patient Narratives on Information Search in a Web-Based Breast Cancer Decision Aid: An Eye-Tracking Study

Abstract: BackgroundPrevious research has examined the impact of patient narratives on treatment choices, but to our knowledge, no study has examined the effect of narratives on information search. Further, no research has considered the relative impact of their format (text vs video) on health care decisions in a single study.ObjectiveOur goal was to examine the impact of video and text-based narratives on information search in a Web-based patient decision aid for early stage breast cancer.MethodsFifty-six women were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
(14 reference statements)
1
32
0
Order By: Relevance
“…876(52.17) status, interaction with peers, knowledge of breast cancer, perception of breast cancer, the existence of breast cancer in the family, the fear of diagnosing breast cancer by BSE, and by the effects of the mass media (Yi et al, 2008;Shaffer et al, 2013;Valero-Aguilera et al, 2014). The results of a study by Yi et al (2008), support the results of the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…876(52.17) status, interaction with peers, knowledge of breast cancer, perception of breast cancer, the existence of breast cancer in the family, the fear of diagnosing breast cancer by BSE, and by the effects of the mass media (Yi et al, 2008;Shaffer et al, 2013;Valero-Aguilera et al, 2014). The results of a study by Yi et al (2008), support the results of the present study.…”
Section: Discussionsupporting
confidence: 81%
“…For this reason it is necessary to evaluate women's health beliefs and increase their motivation (Karayurt and Dramalı, 2007;Avci et al, 2014;Karadag et al, 2014;Yucel et al, 2014). The results of other studies have also shown the effectiveness of education given in the internet on developing a positive health attitude towards protection against breast cancer and early diagnosis of breast cancer, and on increasing women's motivation to practice BSE (Berland et al, 2001;Kim et al, 2001;Baker et al, 2003;Yi et al, 2008;Dang et al, 2013;Shaffer et al, 2013;Valero-Aguilera et al, 2014). In the present study, women's scores on knowledge of breast cancer and BSE increased from 46.52 before the internet education program to 76.73 six months after it.…”
Section: Discussionmentioning
confidence: 99%
“…Educational theory supports the use of videos to increase saliency, but current literature reviews regarding patients' decision support lack robust evidence that videos improve patients? information comprehension or preparation for decision making [67][68][69][70][71][72]. Possible social matching/mismatching (by race, age, or sex) between the viewer and the individuals presented in videos could bias participants?…”
Section: Discussionmentioning
confidence: 99%
“…However, all these recommendations produce extra information, and we should be wary of information overload. Therefore, one might also think of alternative ways to present information, such as video narratives (Shaffer, Owens, & Zikmund-Fisher, 2013).…”
Section: Discussionmentioning
confidence: 99%